Предмет: Алгебра,
автор: sonae323
помоги решить пример очень надо (2x+3)(3-2x)-2(4x-15)-10(2x-1)=33
Ответы
Автор ответа:
0
(2x + 3)(3 - 2x) - 2(4x - 15) - 10(2x - 1) = 33
9 - 4x² - 8x + 30 - 20x + 10 = 33
- 4x² - 28x + 49 = 33
- 4x² - 28x + 49 - 33 = 0
4x² + 28x - 16 = 0
x² + 7x - 4 = 0
D = 49 +16 = 65
X1,2 = ( - 7) + - √65) / 2
X1 = - 7 + √65
X2 = - 7 - √65
9 - 4x² - 8x + 30 - 20x + 10 = 33
- 4x² - 28x + 49 = 33
- 4x² - 28x + 49 - 33 = 0
4x² + 28x - 16 = 0
x² + 7x - 4 = 0
D = 49 +16 = 65
X1,2 = ( - 7) + - √65) / 2
X1 = - 7 + √65
X2 = - 7 - √65
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Музыка,
автор: ignatenkoelizaveta31
Предмет: Литература,
автор: Аноним
Предмет: Математика,
автор: отличница137
Предмет: Математика,
автор: Аноним